Ingenious Italians immigrant artists in eighteenth-century Britain - McHale, Katherine (Harvey Miller, 2024)
"This book fills a significant gap in the literature on eighteenth-century art in Britain. Although immigrant Italian artists played a crucial role in the development of Britain’s expanding art world over the course of that century, they have been largely overlooked in books on both British and Italian art. When mentioned in works on eighteenth-century British art, Italian artists are regarded as bit players who were tangential to the art world. Ingenious Italians seeks to correct this view, demonstrating the critical role played by immigrants who brought their skills and talents to a new country. In Britain, they established networks of Italian and British colleagues, cultivated new patrons and created innovative works for a growing market. In doing so, they influenced the development of art in British society. This little-explored facet of art history in Britain presents readers with a new perspective from which to consider the art of the era, highlighting the important work contributed by Italian artists in Britain. The book also contains an appendix of biographical information on the Italian artists working in Britain throughout the eighteenth century."